2004
DOI: 10.1016/j.jcp.2003.11.028
|View full text |Cite
|
Sign up to set email alerts
|

Data assimilation with an extended Kalman filter for impact-produced shock-wave dynamics

Abstract: Model assimilation of data strives to determine optimally the state of an evolving physical system from a limited number of observations. The present study represents the first attempt of applying the extended Kalman filter (EKF) method of data assimilation to shock-wave dynamics induced by a high-speed impact. EKF solves the full nonlinear state evolution and estimates its associated error-covariance matrix in time. The state variables obtained by the blending of past model evolution with currently available … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
23
0

Year Published

2006
2006
2015
2015

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(23 citation statements)
references
References 28 publications
0
23
0
Order By: Relevance
“…The underlying physical problem stems from a flyer plate experiment [16]. Our results [20] successfully demonstrated that: (1) EKF propagates information through the modelÕs governing equations from observed to unobserved variables as well as locations; (2) EKF should not be considered a curve fitting procedure; carefully assessing both the model and observation errors is crucial in obtaining meaningful results with this method; and (3) a single scalar observation can noticeably reduce the error in estimating the state of the 1-D system with its total number of over 200 discrete variables.…”
Section: Introductionmentioning
confidence: 85%
See 2 more Smart Citations
“…The underlying physical problem stems from a flyer plate experiment [16]. Our results [20] successfully demonstrated that: (1) EKF propagates information through the modelÕs governing equations from observed to unobserved variables as well as locations; (2) EKF should not be considered a curve fitting procedure; carefully assessing both the model and observation errors is crucial in obtaining meaningful results with this method; and (3) a single scalar observation can noticeably reduce the error in estimating the state of the 1-D system with its total number of over 200 discrete variables.…”
Section: Introductionmentioning
confidence: 85%
“…The extended Kalman filter (EKF) method of data assimilation [10,11,15,20] designed to optimize predictions of, as well as reduce uncertainties in, the modeled state variables, provided that the errors in the observations and model performance can be estimated. The EKF algorithm tracks the nonlinear state evolution and its associated error-covariance matrix in time.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Methods to overcome the computational difficulties arising from large covariance matrices involve low-rank and partitioning approximations [19,20], as well as parallelization techniques [21,22]; reviews include [23,24]. At the same time, data assimilation is perceived more and more as a powerful strategy in advancing understanding, simulation and prediction in the earth sciences as a whole [25] and beyond [26].…”
Section: Background and Motivationmentioning
confidence: 99%
“…Kalman Filter was frequently used in the field of meteorology and oceanography (e.g. [9][10][11][12][13][14]). Although a lot of applications are presented in the engineering fields, there are no previous studies of the Kalman Filter based on blasting vibrations.…”
Section: Introductionmentioning
confidence: 99%